The influence of physiological and functional characteristics of the body of girls aged 17-18 years on playing sports - Yerkebulan Tazabek; Zhaxybek Zhunusbekov; Vitaliy Avsiyevich; Aliya Belegova; Batilya Yermenova (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Achieving competitive results in women’s sports for athletes aged 17-18 requires structuring training processes around their physiological characteristics. This article analyzes recent scientific data on the impact of sexual dimorphism in girls aged 17-18 on sports participation and training. Relevant scientific works from the past five years were collected and analyzed. At this age, girls undergo the final stage of sexual maturation. The effectiveness of sports activities varies individually, influenced by the ovarian-menstrual cycle, hormonal background, and symptoms in each cycle phase. Physical activity declines during the menstrual, ovulatory, and premenstrual phases, while postmenstrual and postovulatory phases are more favorable for sports participation. Performance indicators depend on sexual dimorphism: female athletes show unique features in central nervous system activity, high psycho-emotional excitability, and earlier development of somatic and physical qualities compared to males. The skeletal structure in 17-18-year-old female athletes is smaller and shorter, with a wider pelvis and more developed shoulder girdle. These findings can be used by sports schools, rehabilitation specialists, coaches, and sports physicians to adapt and structure training processes, taking into account the physiological characteristics of 17-18-year-old female athletes, aiming for highly competitive results.